Angular distribution of annual collectible radiation on solar cells of CPC based photovoltaic systems. (October 2016) - Yu, Mingjiu; Yu, Yamei; Tang, Runsheng
Highlights: A procedure to estimate angular distribution of annual radiation on absorber of CPC- θ e is suggested. Effects of the geometry of CPC- θ e on the performance of CPV- θ e are investigated. It is seen that angular distribution of annual radiation of NS-CPCs is isotropic but not for EW-CPCs. Abstract: To investigate effects of the geometry of compound parabolic concentrators (CPCs) on the performance of CPC based photovoltaic systems (CPVs), it is necessary to determine the angular distribution of the annual collectible radiation on solar cells as the photovoltaic conversion efficiency of solar cells is highly sensitive to the incident angle of solar rays, especially for radiation incident at the angle larger than 65°. In this work, a mathematical procedure is suggested to estimate the annual collectible radiation and its angular distribution on the absorber of CPC- θ e where the exit angle of solar rays is restricted within θ e for the incoming radiation over its acceptance angle. Calculations show that, given the acceptance half-angle ( θ a ), the annual collectible radiation of full CPC- θ e oriented in the east–west direction (EW-CPC- θ e ) increases with the increase of θ e ; whereas for truncated EW-CPC- θ e with given θ a and geometric concentration ( Ct ), the annual radiation collected by EW-CPC- θ e with θ e  < 90° is almost identical to that by EW-CPC-90, the one without exit angle restriction, even slightly higher. Results indicate that, for CPC- θ e oriented in the north–south direction (NS-CPC- θ e ), the angular distribution of annual collectible radiation can be regarded to be isotropic; whereas for EW-CPC- θ e, the angular distribution is dependent on its geometry and strategy of its tilt-angle adjustment but is anisotropic. Results also reveal that the annual power output from EW-CPV- θ e decrease with the increase of θ e and always higher than that from EW-CPV-90 except full EW-CPV- θ e in the case of aperture's tilt-angle being yearly adjusted four times at three tilts.